2022
DOI: 10.1111/iwj.13763
|View full text |Cite
|
Sign up to set email alerts
|

Effect of enteral immunonutrition compared with enteral nutrition on surgical wound infection, immune and inflammatory factors, serum proteins, and cellular immunity in subjects with gastric cancer undergoing a total gastrectomy: A meta‐analysis

Abstract: We performed a meta‐analysis to evaluate the effect of enteral immunonutrition compared with enteral nutrition on surgical wound infection, immune and inflammatory factors, serum proteins, and cellular immunity in subjects with gastric cancer undergoing a total gastrectomy. A systematic literature search up to November 2021 was done, and 10 studies included 1056 subjects with gastric cancer undergoing a total gastrectomy at the start of the study: 505 of them were provided with enteral immunonutrition, and 551… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…This meta-analysis and systematic review included more randomized, controlled trials and showed different conclusions compared with Fu et al’s study. 26 Fu et al’s study showed that IgG, IgM, and protein concentrations in the EIN group were significantly higher from higher in the EIN group than in the EN group. Our study showed that patients in the EIN group had higher CD8+, proalbumin, and immunoglobulin concentrations, higher CD4+/CD8, and a lower incidence of postoperative infectious complications than those in the EN group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This meta-analysis and systematic review included more randomized, controlled trials and showed different conclusions compared with Fu et al’s study. 26 Fu et al’s study showed that IgG, IgM, and protein concentrations in the EIN group were significantly higher from higher in the EIN group than in the EN group. Our study showed that patients in the EIN group had higher CD8+, proalbumin, and immunoglobulin concentrations, higher CD4+/CD8, and a lower incidence of postoperative infectious complications than those in the EN group.…”
Section: Discussionmentioning
confidence: 99%
“…25 and Fu et al. 26 only focused on patients with gastric cancer who underwent total gastrectomy, and some recent high-quality, randomized, controlled trials were excluded.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to other strategies to improve anticancer immunity, data on the beneficial effects of immunonutrients administered perioperatively are accumulating in GC[ 69 ]. Immunonutrient interventions are nutrition support that is rich in elements beneficial for the homeostasis of immunity, including ω-3-fatty acids, glutamine, arginine, and nucleotides[ 70 ].…”
Section: Potential Perioperative Interventionsmentioning
confidence: 99%
“…For example, Song et al 2015 [ 11 ], Nikniaz et al 2017 [ 12 ], and Cheng et al 2018 [ 13 ] reported in their systematic review and meta-analysis that early administration of EIN in patients was more effective in improving their immunity index and post-surgical nutritional status. Similarly, Fu et al 2021 [ 14 ] and Shen et al 2022 [ 15 ] mentioned in their systematic review and meta-analysis that pre-operative use of EIN was effective and safe in reducing the post-operative infections, overall complications of surgery, and the duration of hospital stay of patients after surgery. These systematic reviews and meta-analysis are based on the results of various randomized controlled trials, and retrospective and prospective studies that were conducted to evaluate the potential benefits of EIN in patients undergoing gastrectomy.…”
Section: Introductionmentioning
confidence: 99%